PENGARUH POLA DIET DASH TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI : LITERATURE REVIEW THE EFFECT OF THE DASH DIET ON BLOOD PRESSURE IN HYPERTENSION PATIENTS - Vidhiastutik, Yusiana (LPPM STIKes Bahrul Ulum Jombang, 2023)
ABSTRACT Introduction:High blood pressure is a disease that has no specific symptoms and is currently still a global health problem. Dietary changes using the DASH diet can be used in hypertensive patients to control blood pressure to reduce the risk of disease complications due to high blood pressure. Objective: The literature review aims to determine the effect of the DASH diet on blood pressure in people with hypertension. Method:. Search for research journals or literature studies on the pages of